Pengawasan Ibadah Shalat Anak Usia SD oleh Orang Tua di Jorong Sariak Kecamatan Luhak Nan Duo Kabupaten Pasaman Barat - Rainis Manita; Iswantir (Humantech : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
This research is motivated by the supervision of prayer services carried out by parents for their children aged 7-12 years, the author took place in Jorong Sariak, Luhak Nan Duo District, West Pasaman Regency, where parents tend to let go of the TPA teacher, parents' work as farmers makes parents forget Regarding their responsibilities, children always argue against their parents and their parents' lack of religion regarding the responsibilities of praying and also parents do not limit their children from using cellphones. This research is a field research (Field research) with a qualitative descriptive approach. Data collection techniques used are observation, interviews using the Snowbal Sampling technique. Key informants consist of children aged 7-12 years and their parents, supporting informants are guardians jorong. The results of the study found (1) the process of monitoring the prayer worship of elementary school-aged children by parents which consisted of setting an example and teaching the procedures for praying, but not all parents did this. (2) Obstacles faced in supervising the prayer services of elementary school-aged children by parents in the form of parents being busy with work, children often arguing with their parents, lack of parental religion regarding prayer worship and parents who let their children play cellphones until they forget the time. (3) How to overcome obstacles in supervising the prayers of elementary school-aged children by parents, namely by parents setting good examples for their children, parents must be aware of their responsibilities, parents must be good at dividing time and limiting children's use of cellphones.